Chemosystematic studies of natural compounds isolated from Asteraceae: characterization of tribes by principal component analysis - Alvarenga, SAV; Ferreira, MJP; Emerenciano, V. P.; Cabrol-Bass, D. (Elsevier B.V., 2001)
This work describes an application of principal component analysis (PCA) on a database of secondary metabolites from the Asteraceae family. The numbers of occurrences of metabolites in 11 chemical classes for the different vibes of the family were used as variables, PCA allows the identification of chemical classes that contribute most to the subgroups classification within the family. Relationships between chemical composition and botanical classification were made. (C) 2001 Elsevier B.V. B.V. All rights reserved.
Keywords: metabolites; botanical classification; family